The Impact of AirAsia's Professional Training and Education and Other Factors on Customer Loyalty - Ng Hee Song; Gadi Dung Paul; Lu Yisi; Ma Jiarui; Ma Zunqi; Liu Sihao; Himanshi Chauhan; Daisy Mui Hung Kee (AIBPM Publisher, 2024)
This study investigates the impact of professional training and education programs on customer loyalty in the airline industry, specifically focusing on AirAsia. With the competitive landscape of the aviation sector, ensuring high levels of customer satisfaction and loyalty is paramount. Data was collected and analyzed from 100 students and 100 community members to explore the impact of professional training and education on customer satisfaction and to deepen the understanding of their relationship. Through a comprehensive analysis of customer feedback, the research examines how employee training enhances service quality, directly influencing customer perceptions and loyalty. Using a quantitative approach, the findings reveal a significant correlation between the effectiveness of training programs and customer loyalty metrics, highlighting the critical role of well-trained employees in delivering superior service experiences. This research contributes to the existing literature by providing empirical evidence supporting the importance of investment in employee development as a strategic tool for enhancing customer loyalty in the competitive airline market. Ultimately, the study underscores the need for airlines to prioritize professional training to maintain a competitive edge and foster lasting relationships with customers.